Method for preparing active kaolinite-series clay through synergistic activation and application of active kaolinite-series clay as auxiliary cementing material
Through collaborative activation technology, thermal activation and mechanochemical activation are combined, and the problem of low activation efficiency of kaolinite clay in the existing technology has been solved, the activity of volcanic ash has been significantly improved, and low-carbon activation and the preparation of high-quality auxiliary gelling materials have been achieved.
Patent Information
- Application Number
- CN202510260635.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-06
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-03-06
AI Technical Summary
The prior art is difficult to effectively activate other clay minerals and non-clay minerals in kaolinite clay, and thermal activation and mechanochemical activation have their own disadvantages, which cannot maximize the volcanic ash activity of kaolinite clay.
The collaborative activation method is used to combine thermal activation with mechanochemical activation, and the thermal activation temperature point is determined through thermal weight loss analysis. After the kaolinite clay is heat-activated, the kaolinite clay is then subjected to the mechanochemical activation treatment of vibration mill to prepare highly active kaolinite clay.
The volcanic ash activity of kaolinite clay has been significantly improved, low-carbon activation has been achieved, high-quality low-carbon auxiliary gelling materials have been prepared, and the mechanical properties of cement mortar have been improved.
Smart Images

Figure CN119822386A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of auxiliary cementitious material production, and in particular relates to a method for preparing active kaolinite clay through synergistic activation and an application of the method as an auxiliary cementitious material. Background Art
[0002] Kaolinite clay is a type of natural clay with kaolinite as the main clay mineral component, which contains other clay minerals and non-clay minerals. Kaolinite has a 1:1 (TO) structure of a layer of silicon-oxygen tetrahedron sandwiched by a layer of aluminum-oxygen octahedron. Kaolinite clay can generally only be used as an inert material when added to cement. If its activity is to be increased, it needs to be activated by effective means. The activation system generally includes thermal activation and mechanochemical activation. Optimizing the activation process can produce clay minerals with higher activity. Compared with other clays, kaolinite clay has a wide distribution range, a low thermal activation temperature, and its calcined product is an excellent source of activated alumina. Therefore, kaolinite activated clay has great potential for use as supplementary cementitious materials (SCMs) and has good mechanical properties.
[0003] Kaolinite clay is generally thermally activated by high-temperature calcination. By dehydrating, dehydroxylating and amorphizing the main clay mineral kaolinite, a metakaolinite phase structure with strong structural variability and highly localized changes in the distribution of Al atoms is formed, which greatly improves the volcanic ash activity. The dehydroxylation temperature of kaolinite is 400-600℃, which is lower than the dehydroxylation temperature of 2:1 clay minerals such as montmorillonite and illite, which are two layers of silicon-oxygen tetrahedrons sandwiching one layer of aluminum-oxygen octahedron. Currently, the method of calcining kaolinite clay at 700-800℃ is often used to prepare active kaolinite clay. Studies have found that mechanochemical activation can use the stress interactions such as compression, shear (friction), impact and collision during mechanical grinding to induce physical changes, changes in crystal state and chemical changes in materials; mechanochemical activation has a significant effect on changing the crystal form and silicon-aluminum structure of clay minerals, which can effectively promote the stratification, dehydroxylation and amorphization of clay minerals, resulting in the enrichment of surface Al, and significantly improving the volcanic ash activity. Both activation methods have certain effects on improving the volcanic ash activity of kaolinite clay, but they also have certain disadvantages.
[0004] Calcination of kaolinite clay requires relatively high temperature, which is not in line with the concepts of low carbon, environmental protection and low energy consumption. Pure mechanical chemical activation is generally carried out by ball milling, planetary ball milling and vibration grinding. Not only does it take a long time and have low efficiency to achieve good volcanic ash activity, but grinding for too long will reduce the volcanic ash activity of clay minerals. In addition, the thermal activation temperature of other clay minerals in kaolinite clay, such as montmorillonite and illite, is higher than that of kaolinite. The calcination temperature of kaolinite to achieve the best thermal activation is not enough to dehydroxylate and amorphize 2:1 clay minerals such as montmorillonite and illite in the clay. If the calcination temperature is increased to ensure that 2:1 clay minerals such as montmorillonite and illite reach the thermal activation temperature, kaolinite will recrystallize at this temperature, and the volcanic ash activity will be reduced. Thermal activation cannot give full play to the volcanic ash activity advantages of all clay minerals, and non-clay mineral phases such as feldspar and quartz do not contribute to the volcanic ash activity of clay under the thermal activation system. Therefore, thermal activation can no longer maximize the volcanic ash activity of kaolinite clay. Summary of the invention
[0005] In order to solve the above technical problems, the present invention proposes a method for preparing active kaolinite clay by synergistic activation and its application as an auxiliary cementitious material. On the basis of thermal activation, the present invention combines mechanochemical activation to synergistically treat kaolinite clay, gives full play to the advantages of thermal activation and mechanochemical activation, maximizes the activity of clay minerals and non-clay minerals in kaolinite clay, realizes low-carbonization activation of kaolinite clay, and provides technical guarantee for the preparation of auxiliary cementitious materials (SCMs).
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] The present invention provides a method for preparing active kaolinite clay by synergistic activation, comprising the following steps:
[0008] Performing a thermogravimetric analysis on the kaolinite clay, taking the peak temperature of the first-order thermogravimetric curve of the kaolinite clay as the thermal activation temperature point, and performing a thermal activation treatment on the kaolinite clay;
[0009] The kaolinite clay after the thermal activation treatment is subjected to a mechanochemical activation treatment to obtain the active kaolinite clay.
[0010] Kaolinite clay is widely distributed, and its activated product is an excellent source of activated alumina, which can be used to prepare new auxiliary cementitious materials. The current high-temperature calcination thermal activation system is difficult to effectively activate other clay minerals and non-clay minerals in kaolinite clay; while the mechanochemical activation system has the problems of long time and high energy consumption. The method of the present invention combines the thermal activation system with the mechanochemical activation system to synergistically treat kaolinite clay, which can significantly improve the activity of volcanic ash while achieving low-carbon activation, thereby preparing high-quality low-carbon auxiliary cementitious materials.
[0011] The kaolinite-based clay consists of 1:1 type kaolinite, other clay minerals and non-clay minerals.
[0012] Furthermore, the peak temperature of the first-order thermal gravimetric loss curve of the kaolinite clay is 525°C.
[0013] Furthermore, during the thermal activation treatment, the heating rate is 10°C / min and the holding time is 2h.
[0014] Furthermore, the mechanochemical activation treatment is a vibration mill.
[0015] Furthermore, the vibration mill adopts the following conditions: frequency is 50 Hz, power is 1.1 kW, and rotation speed is 1420 rpm.
[0016] Furthermore, the grinding time of the vibration mill is 20-100 min.
[0017] Preferably, the grinding time of the vibration mill is 20-40 min, more preferably the grinding time is 40 min.
[0018] The present invention also provides an activated kaolinite clay prepared by the method.
[0019] The present invention also provides the use of the active kaolinite clay as an auxiliary gelling material.
[0020] The present invention also provides a method for preparing cement mortar using the above-mentioned active kaolinite clay: PI cement, water, standard sand and the active kaolinite clay are evenly mixed, the active kaolinite clay is used as an auxiliary cementitious material to replace 20% of the PI cement by mass fraction, and the cement mortar is obtained after curing.
[0021] Exemplarily, the method for preparing cement mortar using the above-mentioned active kaolinite clay is as follows: weigh 360g of PI cement, 90g of active kaolinite clay, 225g of mixing water, and 1350g of standard sand, add the above materials into a planetary cement mortar mixer, stir them thoroughly, mix them evenly, and obtain a mortar;
[0022] The cement mortar is poured into a 40*40*1600mm mold, fully tamped, and vibrated on a compaction table for 60s. After the surface is smoothed, it is placed in a constant temperature and humidity curing box for curing to obtain the cement mortar.
[0023] Compared with the prior art, the present invention has the following advantages and technical effects:
[0024] The present invention uses mechanochemical activation in conjunction with thermal activation to treat kaolinite clay, so that the particles are crushed and the specific surface area is significantly increased, while accelerating the transformation of the Al coordination form in kaolinite, that is, from hexacoordination (Al(6)) to pentacoordination (Al(5)) and tetracoordination (Al(4)). Mechanochemical activation after thermal activation treatment breaks the H bonds of adjacent kaolinite layers, increases the degree of structural disorder, and weakens the OH bonding, thereby reducing the temperature of dehydroxylation; porous aggregates are formed on the mineral surface after mechanical activation, which are more likely to adsorb air water molecules, resulting in a significant increase in weight loss within the range of 50-200°C. Synergistic activation can significantly promote the complete delamination, dehydroxylation and amorphization of kaolinite, and can enhance the volcanic ash activity of kaolinite clay compared to single thermal activation or mechanical activation.
[0025] The product (i.e., active kaolinite clay) prepared by mechanochemical activation and synergistic thermal activation is used as an auxiliary cementitious material to replace PI cement with a mass fraction of 20%. The 7-day (7d) and 28-day (28d) compressive strengths of the cement mortar test block are 43.8MPa and 53.2MPa, respectively, and the strength activity index (SAI) values are both above 100%. This is attributed to the auxiliary cementitious material formed by synergistic activation, the active kaolinite clay, which has stronger volcanic ash activity and higher consumption of calcium hydroxide. The hydration products formed have more content of monosulfur hydrated calcium sulfoaluminate (AFm phase), hydrated calcium aluminum feldspar, and hydrated calcium silicate (aluminum) gel (C-(A)-SH), thereby making the microstructure of the cementitious system more compact.
[0026] The present invention adopts a synergistic activation method to treat kaolinite clay, which is an effective method for activating clay minerals, can improve the activation efficiency of clay minerals and non-clay minerals, achieve low-carbon activation of clay resources, and alleviate the problems of insufficient supply and high cost of traditional auxiliary cementitious materials. It is in line with the demand for environmentally friendly materials advocated by modern society and the goal of sustainable development. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:
[0028] Figure 1 It is the thermogravimetric and first-order thermogravimetric analysis diagram of kaolinite clay raw materials;
[0029] Figure 2 It is the particle size distribution diagram of the products of comparative examples 1-4 and embodiments 1-5;
[0030] Figure 3 Microscopic morphology of the product of Comparative Example 1;
[0031] Figure 4 This is a microscopic morphology of the product of Comparative Example 2;
[0032] Figure 5 This is a microscopic morphology of the product of Comparative Example 3;
[0033] Figure 6 This is a microscopic morphology of the product of Example 1;
[0034] Figure 7 This is a microscopic morphology of the product of Example 2;
[0035] Figure 8 This is a microscopic morphology of the product of Example 3;
[0036] Fig. 9 This is a microscopic morphology of the product of Example 4;
[0037] Fig.10 This is a microscopic morphology of the product of Example 5;
[0038] Fig.11 This is a microscopic morphology of the product of Comparative Example 4;
[0039] Fig.12 For the products of Comparative Examples 1-4 and Examples 1-5 27 Al solid state NMR spectrum ( 27 Al SSNMR) map;
[0040] Fig.13 It is the X-ray diffraction (XRD) analysis spectrum of the products of Comparative Examples 1-4 and Examples 1-5. DETAILED DESCRIPTION
[0041] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0042] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0043] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0044] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0045] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0046] An embodiment of the present invention provides a method for preparing active kaolinite clay by synergistic activation, comprising the following steps:
[0047] The kaolinite clay was subjected to thermogravimetric analysis. The peak temperature (525°C) of the first-order thermogravimetric curve of the kaolinite clay was taken as the thermal activation temperature point. The kaolinite clay was subjected to thermal activation treatment. During the thermal activation treatment, the heating rate was 10°C / min and the holding time was 2h.
[0048] The kaolinite clay after the thermal activation treatment is subjected to a mechanochemical activation treatment by a vibration mill to obtain an activated kaolinite clay, and the vibration mill adopts the following conditions: a frequency of 50 Hz, a power of 1.1 kW, and a rotation speed of 1420 rpm. The grinding time of the vibration mill is 20-100 min, preferably 20-40 min, and more preferably 40 min.
[0049] Kaolinite clay is widely distributed, and its activated product is an excellent source of activated alumina, which can be used to prepare new auxiliary cementitious materials. The current high-temperature calcination thermal activation system is difficult to effectively activate other clay minerals and non-clay minerals in kaolinite clay; while the mechanochemical activation system has the problems of long time and high energy consumption. The method of the present invention combines the thermal activation system with the mechanochemical activation system to synergistically treat kaolinite clay, which can significantly improve the activity of volcanic ash while achieving low-carbon activation, thereby preparing high-quality low-carbon auxiliary cementitious materials.
[0050] During the calcination process, kaolinite will undergo dehydration, dehydroxylation and recrystallization. The dehydration stage refers to the temperature range of 0-200°C, during which various water molecules adsorbed in pores, structural channels or bonded to interlayer cations are released, and the crystal structure of each mineral phase in kaolinite will not be destroyed. The dehydroxylation stage is 400-600°C, during which kaolinite will remove hydroxyls, the crystal structure will be destroyed, the silicon-oxygen tetrahedron and aluminum-oxygen octahedron structures will change, and eventually it will be transformed into an amorphous aluminosilicate phase metakaolinite structure with volcanic ash activity. The phase transition stage such as recrystallization is when the thermal activation temperature is higher than 900°C, when the potentially active phase of metakaolinite transforms to a stable phase and a higher temperature phase. It is a stage in which the volcanic ash activity is significantly reduced. At 925°C, metakaolinite is transformed into aluminum-silicon spinel (Al 2 O 3 ·3SiO 2 ) crystals and produce amorphous SiO 2 , alumina-silicon spinel transforms into pseudo-mullite (Al 2 O 3 ·SiO 2 ), when the calcination temperature rises to 1300℃, it transforms into mullite (3Al 2 O 3 ·2SiO 2 ) and cristobalite. The thermal activation temperature of kaolinite clay is generally selected to be a temperature at which the kaolinite clay is completely dehydroxylated but has not reached recrystallization, usually 600-800°C, to ensure that the amorphization degree of the kaolinite clay is high, but this temperature is not enough to enhance the activity of other 2:1 clay minerals and non-clay minerals in the kaolinite clay, and the calcination temperature is relatively high, which does not meet the low-carbon and environmentally friendly properties. Therefore, the present invention selects a lower thermal activation temperature point (the peak temperature point of kaolinite dehydroxylation), supplemented by mechanochemical activation, to maximize the volcanic ash activity of the kaolinite clay while simultaneously activating the kaolinite clay with low carbonization.
[0051] In the following embodiments and comparative examples of the present invention, kaolinite clay is composed of 1:1 type kaolinite, other clay minerals and non-clay minerals. 1:1 type kaolinite refers to a layered silicate mineral whose structural unit layer is composed of silicon oxygen tetrahedron (Si-O tetrahedron) and aluminum oxygen octahedron (Al-(O,OH) octahedron).
[0052] The active kaolinite-based clay provided in the embodiment of the present invention can be used as an auxiliary cementitious material to prepare cement mortar.
[0053] An embodiment of the present invention also provides a method for preparing cement mortar using the above-mentioned active kaolinite clay: PI cement, water, standard sand and active kaolinite clay are evenly mixed, and the active kaolinite clay is used as an auxiliary cementitious material to replace 20% of the PI cement by mass, and cement mortar is obtained after curing.
[0054] Exemplarily, the method for preparing cement mortar using the above-mentioned active kaolinite clay is as follows: weigh 360g of PI cement, 90g of active kaolinite clay, 225g of mixing water, and 1350g of standard sand, add the above materials into a planetary cement mortar mixer, stir them thoroughly, mix them evenly, and obtain a mortar;
[0055] Pour the glue mortar into a 40*40*1600mm mold, tamp it thoroughly, vibrate it on a compaction table for 60s, smooth the surface, and put it in a constant temperature and humidity curing box for curing to obtain cement mortar.
[0056] In the following embodiments and comparative examples of the present invention, the flexural and compressive strengths of the mortar test blocks were measured according to "GB / T 17671-2021 Test method for strength of cement mortar (ISO method)", and the strength activity index was measured according to EN196-1:2016.
[0057] Kaolinite clay is widely distributed, and its activated product is an excellent source of activated alumina, which can be used to prepare new auxiliary cementitious materials. The current high-temperature calcination thermal activation system is difficult to effectively activate other clay minerals and non-clay minerals in kaolinite clay; while the mechanochemical activation system has the problems of long time and high energy consumption. The method of the present invention combines the thermal activation system with the mechanochemical activation system to synergistically treat kaolinite clay, which can significantly improve the activity of volcanic ash while achieving low-carbon activation, thereby preparing high-quality low-carbon auxiliary cementitious materials.
[0058] In the following examples and comparative examples of the present invention, the kaolinite clay is composed of 1:1 type kaolinite, other clay minerals and non-clay minerals. The chemical composition of the kaolinite clay and the silicate cement with a strength grade of 42.5R (PI 42.5R) is shown in Table 1. The kaolinite content in the kaolinite clay is 95.8%, the illite content is 1.0%, and the quartz content is 3.2%.
[0059] Table 1 Chemical composition of raw materials (mass percentage)
[0060] Chemical composition <![CDATA[SiO 2 ]]> <![CDATA[Al 2 THE 3 ]]> <![CDATA[Fe 2 THE 3 ]]> CaO MgO <![CDATA[SO 3 ]]> <![CDATA[Na 2 The]]> Loss on ignition Kaolinite clay 36.59 29.82 0.94 0.02 0.05 0.15 0.31 13.99 PI 42.5R 20.16 4.68 3.51 62.49 4.04 2.30 0.71 0.046
[0061] Unless otherwise specified, the room temperature in the present invention is 25±2°C.
[0062] It should be pointed out that the matters not described in detail in the present invention are all conventional operating means in the art and are not the focus of the present invention. For example, specific methods such as thermogravimetric analysis are all carried out using conventional methods.
[0063] The technical solution of the present invention is further illustrated by the following embodiments.
[0064] Example 1
[0065] This embodiment provides a method for preparing active kaolinite clay through synergistic activation, and the specific steps are as follows:
[0066] (1) After drying the kaolinite clay at 105°C, a thermogravimetric analysis was performed using a thermogravimetric analyzer ( Figure 1 ), the peak temperature of the first-order thermal weight loss curve of 525°C was selected as the thermal activation temperature point, and the thermal activation treatment was carried out by calcining in a muffle furnace. In the thermal activation treatment: the kaolinite clay was placed in an alumina square box and calcined at 525°C for 2h with a heating rate of 10°C / min; after thermal activation, the alumina square box was transferred out of the muffle furnace, and the obtained product was spread on a steel plate and cooled under natural environmental conditions;
[0067] (2) A vibration mill with a frequency of 50 Hz, a power of 1.1 kW, and a rotation speed of 1420 rpm was further used for mechanochemical activation treatment. Each mechanochemical activation treatment was performed on 50 g of sample and the sample was ground for 20 min. The ground powder was the activated kaolinite clay. The ground powder was immediately transferred to a sealed bag and stored at room temperature.
[0068] Example 2
[0069] Same as Example 1, except that the grinding time in step (2) is 40 min.
[0070] Example 3
[0071] Same as Example 1, except that the grinding time in step (2) is 60 min.
[0072] Example 4
[0073] Same as Example 1, except that the grinding time in step (2) is 80 min.
[0074] Example 5
[0075] Same as Example 1, except that the grinding time in step (2) is 100 min.
[0076] Comparative Example 1
[0077] The kaolinite clay was dried at 105°C.
[0078] Comparative Example 2
[0079] After the kaolinite clay was dried at 105°C, a thermogravimetric analysis was performed using a thermogravimetric analyzer, and the peak temperature of the first-order thermogravimetric curve of 525°C was selected as the thermal activation temperature point for thermal activation treatment. During the thermal activation treatment: the kaolinite clay was placed in an alumina square box and calcined at 525°C for 2h with a heating rate of 10°C / min; after thermal activation, the alumina square box was transferred out of the muffle furnace, and the obtained product was spread on a steel plate and cooled under natural environmental conditions to obtain active kaolinite clay, which was then sealed and preserved.
[0080] Comparative Example 3
[0081] After the kaolinite clay was dried at 105°C, a thermogravimetric analysis was performed using a thermogravimetric analyzer, and the complete dehydroxylation temperature of 750°C was selected as the thermal activation temperature point for thermal activation treatment. During the thermal activation treatment: the kaolinite clay was placed in an alumina square box and calcined at 750°C for 2h with a heating rate of 10°C / min; after thermal activation, the alumina square box was transferred out of the muffle furnace, and the obtained product was spread on a steel plate and cooled under natural environmental conditions to obtain active kaolinite clay, which was then sealed and preserved.
[0082] Comparative Example 4
[0083] After drying the kaolinite clay at 105°C, a vibration mill with a frequency of 50 Hz, a power of 1.1 kW, and a rotation speed of 1420 rpm was used for mechanochemical activation treatment. Each mechanochemical activation treatment was performed on 50 g of sample and ground for 100 min. The ground powder sample was the activated kaolinite clay, which was immediately transferred to a sealed bag and stored at room temperature.
[0084] The activation systems of Examples 1-5 and Comparative Examples 1-4 are detailed in Table 2.
[0085] Table 2 Activation system
[0086] Group Revitalization system Activation temperature(℃) Activation time Example 1 Synergistic Activation Heat activated 525 Calcination holding time 2h + mechanical grinding 20min Example 2 Synergistic Activation Heat activated 525 Calcination holding time 2h + mechanical grinding 40min Example 3 Synergistic Activation Heat activated 525 Calcination holding time 2h + mechanical grinding 60min Example 4 Synergistic Activation Heat activated 525 Calcination holding time 2h + mechanical grinding 80min Example 5 Synergistic Activation Heat activated 525 Calcination holding time 2h + mechanical grinding 100min Comparative Example 1 Not activated - - Comparative Example 2 Thermal Activation 525 Calcination holding time 2h Comparative Example 3 Thermal Activation 750 Calcination holding time 2h Comparative Example 4 Mechanochemical activation 25 Mechanical grinding 100min
[0087] The products of the above-mentioned embodiments and comparative examples were subjected to laser particle size distribution measurement, microscopic morphology test, 27 Al solid NMR test ( 27 Al SSNMR), X-ray diffraction phase analysis (XRD) and volcanic ash activity test. The particle size distribution results of the products of each embodiment and comparative example are shown in Table 3.
[0088] Table 3 Particle size distribution of active kaolinite clay in Examples 1-5 and Comparative Examples 1-4
[0089] Example 1 Example 2 Example 3 Example 4 Example 5 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 D10(μm) 0.99 1.04 1.00 0.96 0.85 0.92 1.03 1.67 0.89 D50(μm) 4.12 4.55 4.05 3.65 2.60 3.22 5.27 48.74 2.95 D90(μm) 40.26 42.98 39.47 36.09 28.99 98.22 106.21 127.26 30.59
[0090] According to the particle size distribution of kaolinite clay after synergistic activation treatment ( Figure 2 ) and microscopic morphology results ( Figure 3-Figure 11 ), it can be seen that the unactivated kaolinite presents a hexagonal layered stacking structure, and calcination at 525℃ and 750℃ has no obvious effect on the layered structure. Calcination at higher temperatures will lead to sintering and agglomerate formation, resulting in an increase in the average particle size. Further mechanochemical activation treatment leads to particle crushing and a significant increase in specific surface area, but grinding for a certain time will lead to the formation of porous aggregates.
[0091] The products of each embodiment and comparative example 27 Al SSNMR results are as follows Fig.12 As shown, it can be seen that comparative example 1 is mainly a 6-coordinated Al structure (Al(6)) with a chemical shift range of 0-20ppm; comparative example 2 shows that the Al structure is still Al(6), and the peak intensities of the five-coordinated and four-coordinated Al (Al(5) and Al(4)) are not obvious; comparative example 3 shows that the Al structure is Al(6), Al(5) and Al(4) structures with chemical shifts of 0-10, 10-40, and 30-60ppm, and the Al(5) peak intensity is the highest; in comparative example 4, the Al coordination structure includes Al(6), Al(5) and Al(4), among which the Al(6) peak intensity is the highest; for the embodiments, the Al(6) peak intensity in embodiment 1 is higher than that of Al(5) and Al(4), and with the increase of grinding time, the peak intensity of Al(6) with a chemical shift of 0-20ppm in embodiments 2-5 decreases, and the peak intensities of Al(5) and Al(4) with a chemical shift of 10-40 and 30-60ppm gradually increase. All the results showed that thermal activation and mechanochemical activation changed the Al coordination number. The aluminum structure of kaolinite was octahedral before activation, and the octahedron transitioned to pentahedron and tetrahedron after activation. The synergistic activation accelerated the transformation of the Al coordination form of kaolinite from Al(6) to Al(5) and Al(4), and the peak contents of Al(5) and Al(4) increased with the increase of grinding time.
[0092] The XRD test results of the products of each embodiment and comparative example are as follows: Fig.13 As shown in the figure, under calcination at 525℃, the diffraction peak intensity of kaolinite (0,0,1) decreases significantly, indicating that calcination at 525℃ causes obvious interlayer damage to kaolinite; after calcination at 750℃, except for a small amount of diffraction peak of quartz phase that has not disappeared, the crystal structure of kaolinite has changed into an amorphous phase; after calcination at 525℃ and then grinding for different times, it is shown that the kaolinite phase reaches an amorphous state after grinding for 40 minutes, and extending the grinding time has no further effect on the amorphous state.
[0093] Volcanic ash activity test takes R 3 Combined with water test method, in which R3 The tested active clay, calcium hydroxide, potassium sulfate, potassium hydroxide and water were mixed in proportions of 6.25g, 18.75g, 0.815g, 0.07g and 30g, respectively. After mixing, they were cured in a 40°C water bath for 7 days, then dried at 110°C to constant weight, and then burned in a muffle furnace to 350°C, kept warm for 1 hour, and weighed to calculate the bound water content. Table 4 lists the volcanic ash activity test results of each embodiment and comparative example. The higher the bound water content, the stronger the volcanic ash activity of the sample.
[0094] Table 4 Kaolinite clay R 3 Combined water content test results
[0095]
[0096] Compared with the pure thermally activated samples, the synergistic effect of thermal activation and mechanochemical activation helps to improve the volcanic ash reactivity. The samples with the highest bound water content are Examples 2 and 3, both of which have the same bound water content of 11.61%. Long-term mechanical grinding reduces the bound water content, indicating that long-term mechanochemical activation is not conducive to further improving the volcanic ash activity. Based on the physicochemical characterization and volcanic ash activity results of all the above examples and comparative examples, Example 2, that is, kaolinite clay calcined at 525°C and mechanically ground for 40 minutes, is selected to replace 20% PI cement by mass as an auxiliary cementitious material.
[0097] Example 6
[0098] This embodiment provides an application of active kaolinite clay as an auxiliary cementitious material. The active kaolinite clay prepared in Example 2 is used as an auxiliary cementitious material to prepare cement mortar. The specific steps are as follows:
[0099] (1) Weigh 360 g of PI cement, 90 g of the activated kaolinite clay of Example 2, 225 g of mixing water, and 1350 g of standard sand, add the above materials into a planetary cement mortar mixer, stir thoroughly, and mix evenly;
[0100] (2) Pour the mortar into a 40*40*1600mm mold, tamp it thoroughly, and vibrate it on a compaction table for 60 seconds. After smoothing the surface, put it in a constant temperature and humidity curing box for 24 hours, then demold it and water-cure it to the ages of 3d, 7d and 28d. The flexural strength, compressive strength and strength activity index of the mortar specimens at each age were tested.
[0101] Comparative Example 5
[0102] (1) Weigh 450 g of PI cement, 225 g of mixing water, and 1350 g of standard sand by weight, add the above materials into a planetary cement mortar mixer, and stir thoroughly to mix evenly.
[0103] (2) Pour the mortar into a 40*40*1600mm mold, tamp it thoroughly, and vibrate it on a compaction table for 60 seconds. After smoothing the surface, put it in a constant temperature and humidity curing box for 24 hours, then demold it and water-cure it to the ages of 3d, 7d and 28d. The flexural strength, compressive strength and strength activity index of the mortar specimens at each age were tested.
[0104] Comparative Example 6
[0105] (1) Weigh 360 g of PI cement, 90 g of quartz sand, 225 g of mixing water, and 1350 g of standard sand by weight, add the above materials into a planetary cement mortar mixer, and stir thoroughly to mix evenly.
[0106] (2) Pour the mortar into a 40*40*1600mm mold, tamp it thoroughly, and vibrate it on a compaction table for 60 seconds. After smoothing the surface, put it in a constant temperature and humidity curing box for 24 hours, then demold it and water-cure it to the ages of 3d, 7d and 28d. The flexural strength, compressive strength and strength activity index of the mortar specimens at each age were tested.
[0107] Comparative Example 7
[0108] (1) Weigh 360 g of PI cement, 90 g of kaolinite clay raw material (i.e., kaolinite clay in Comparative Example 1), 225 g of mixing water, and 1350 g of standard sand in a planetary cement mortar mixer, and stir thoroughly to mix evenly.
[0109] (2) Pour the mortar into a 40*40*1600mm mold, tamp it thoroughly, and vibrate it on a compaction table for 60 seconds. After smoothing the surface, put it in a constant temperature and humidity curing box for 24 hours, then demold it and water-cure it to the ages of 3d, 7d and 28d. The flexural strength, compressive strength and strength activity index of the mortar specimens at each age were tested.
[0110] Comparative Example 8
[0111] (1) Weigh 360 g of PI cement, 90 g of the active kaolinite clay of Comparative Example 2, 225 g of mixing water, and 1350 g of standard sand in parts by weight, add the above materials into a planetary cement mortar mixer, stir thoroughly, and mix evenly.
[0112] (2) Pour the mortar into a 40*40*1600mm mold, tamp it thoroughly, and vibrate it on a compaction table for 60 seconds. After smoothing the surface, put it in a constant temperature and humidity curing box for 24 hours, then demold it and water-cure it to the ages of 3d, 7d and 28d. The flexural strength, compressive strength and strength activity index of the mortar specimens at each age were tested.
[0113] Comparative Example 9
[0114] (1) Weigh 360 g of PI cement, 90 g of the active kaolinite clay of Comparative Example 3, 225 g of mixing water, and 1350 g of standard sand in parts by weight, add the above materials into a planetary cement mortar mixer, and stir thoroughly to mix evenly.
[0115] (2) Pour the mortar into a 40*40*1600mm mold, tamp it thoroughly, and vibrate it on a compaction table for 60 seconds. After smoothing the surface, put it in a constant temperature and humidity curing box for 24 hours, then demold it and water-cure it to the ages of 3d, 7d and 28d. The flexural strength, compressive strength and strength activity index of the mortar specimens at each age were tested.
[0116] The test results of the flexural strength, compressive strength and strength activity index of the mortar test blocks of Example 6 and Comparative Examples 5-9 at various ages are shown in Table 5.
[0117] Table 5 Flexural strength, compressive strength and strength activity index of mortar specimens at different ages
[0118]
[0119] The above results show that the stronger the volcanic ash activity of the kaolinite clay sample, the greater the consumption of portlandite, and the higher the strength activity index (SAI). The compressive strength of the cement mortar test block of Example 6 exceeded that of PI cement at 7d and 28d, reaching 43.8MPa and 53.2MPa respectively, showing outstanding mechanical properties. The excellent mechanical properties show that mechanochemical synergistic thermal activation can effectively promote kaolinite clay to form an auxiliary cementitious material with high volcanic ash activity. This process consumes more portlandite and generates more hydration products, such as C-(A)-SH gel (calcium-(aluminum)-silicate hydrated gel), AFm phase (monosulfur hydrated calcium sulfoaluminate) and hydrated calcium aluminum feldspar, thereby improving the macroscopic mechanical strength and making the microstructure more compact.
[0120] The above are only preferred specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for preparing active kaolinite clay by synergistic activation, characterized in that: The following steps are involved: Performing a thermogravimetric analysis on the kaolinite clay, taking the peak temperature of the first-order thermogravimetric curve of the kaolinite clay as the thermal activation temperature point, and performing a thermal activation treatment on the kaolinite clay; The kaolinite clay after the thermal activation treatment is subjected to a mechanochemical activation treatment to obtain the active kaolinite clay.
2. The method for preparing active kaolinite clay by synergistic activation according to claim 1, characterized in that: The peak temperature of the first-order thermal weight loss curve of the kaolinite clay is 525°C.
3. The method for preparing active kaolinite clay by synergistic activation according to claim 1, characterized in that: During the thermal activation treatment, the heating rate is 10°C / min and the heat preservation time is 2h.
4. The method for preparing active kaolinite clay by synergistic activation according to claim 1, characterized in that: The mechanochemical activation treatment is a vibration mill.
5. The method for preparing active kaolinite clay by synergistic activation according to claim 4, characterized in that: The vibration mill adopts the following conditions: frequency is 50 Hz, power is 1.1 kW, and rotation speed is 1420 rpm.
6. The method for preparing active kaolinite clay by synergistic activation according to claim 4, characterized in that: The grinding time of the vibration mill is 20-100 min.
7. The method for preparing active kaolinite clay by synergistic activation according to claim 6, characterized in that: The grinding time of the vibration mill is 20-40 minutes.
8. An activated kaolinite clay, characterized in that: Prepared according to the method according to any one of claims 1 to 7.
9. Use of the active kaolinite clay according to claim 8 as an auxiliary gelling material.
10. A method for preparing cement mortar using the activated kaolinite clay according to claim 8, characterized in that: PI cement, water, standard sand and the active kaolinite clay are uniformly mixed, the active kaolinite clay is used as an auxiliary cementitious material to replace 20% of the PI cement by mass fraction, and the cement mortar is obtained after curing.
Citation Information
Patent Citations
Method for synthesizing sodalite zeolite molecular sieve from coal gangue solid waste
CN113307282A
Multi-element low-carbon less-clinker composite cement and preparation method thereof
CN114920473A
Comprehensive coal gangue analysis method
CN115980309A
Additive for increasing short-term mechanical strength of hydraulic compositions with lower clinker content
CN117529460A
Method for preparing cement admixture by activating coal gangue powder at low temperature
CN118184204A
Cited By
A method and apparatus for activation of clays using a combined thermal and mechanical process
DK182467B1
A method for activation of clays using a combined thermal and mechanical process
DK202530570A1